Chromogenic and fluorogenic detection of copper ions in the solution and intracellular media. Issue 5 (18th December 2018) - Hanif, Muhammad; Rafiq, Muhammad; Saleem, Muhammad; Mustaqeem, Muhammad; Jamil, Saba; Janjua, Muhammad Ramzan Saeed Ashraf
Abstract : The development of a fluorescent sensor for the trace detection of the metallic contamination in the ecosystem and biological media have been a demand to reduce the health risk and environmental protection. Herein, we report the synthesis of 2‐formyl‐5‐picolinyl‐substituted rhodamine B derivative through Schiff base formation for the trace detection of the copper ions in the aqueous organic media as well as inside the live cells via bioimaging experiments. The ligand was successfully employed to detect the minute copper level ratiometrically through the chromogenic and fluorogenic response. The detection limit of the sensor was found to be 0.54 × 10 −9 mol/L using 3 σ /slope relations. The reversible behavior of the ligand copper complex was determined using sulfide ions that regenerate the entire native properties of the ligands by snatching copper from the complex. The bioimaging experimental results represent the efficient membrane permeability of ligands with the minimum level of toxicity in the measured range found by the MTT assay. The appearance of bright red fluorescence from the BHK‐21 (hamster kidney fibroblast) cells upon treatment of the ligand incubated cells with the copper ions represents the utility of the proposed sensor for the copper detection probe in the intracellular media. Abstract : The fluorescence titration of ligand 3 (0.5 μM) at emission maxima of 591 nm as a function of copper concentration (0.2–1 eq), the inset describes the fluorescence enhancement at emission maxima of 591 nm. The results exhibited the noticeable chromogenic and fluorogenic response of the ligand solution on treatment with copper ions giving indication of the ligand‐copper complexation.